Evaluating the Effect of Earthquake Vertical Component on Large Bay Steel Gabled Frame Located on Flexible Substrate using IDA - Mohammad Malekizadeh (Iranian Society of Structrual Engineering (ISSE), 2019)
Because Steel Gabled Frame, SGF, is essentially a lightweight, in most cases, in addition to the horizontal earthquake component, their vertical component is also ignored. That's while with an increase of SGF bay, structural mass increases significantly and as a Result, vertical motion can produce large inertial forces in the structural members. Previous research shows destructive effects of this component in both concrete and steel structure systems, but so far the effect of earthquake vertical component on SGF has not been Studied before. Therefore this paper could open a new window of study on this type of Structure against both horizontal and vertical motions. Moreover, reviewing the behavior of SGF under the effect of Soil-Structure Interaction (SSI) can help to achieve the better understanding of the SGF Structural Behavior. For this purpose, in this research 4 types of SGF with 20 and 60 m span, and 6 and 12 m height has been considered. Incremental Dynamic Analysis (IDA) with and without regard to the effects of the vertical component as well as SSI was conducted. Then, results were presented in the form of fragility curves at three different performance levels. Results Indicate that vertical component of an earthquake has an important and decisive role in the behavior of SGFs. For example, with considering both vertical and horizontal motion effects, the SGFs enters nonlinear region immediately in comparison with considering horizontal component only. Moreover, reducing the capacity and increasing the probability of fragility and collapse are the most important effects of vertical and horizontal motion simultaneously. But, Consider Soil-Structural Interaction has a less impact on the seismic behavior of SGFs.